Protection of Community Rights In The Process of Issuing Building Permits In Tanggamus Regency, Lampung Province - Dadang Supriatna; Florianus Aser; Nurul Mutmainnah Jamil (Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to analyze the impact of the issuance of Building Permits (IMB) on legal protection for the community in Tanggamus Regency, Lampung Province. The background of the research is based on the low public awareness of the importance of obtaining a building permit, along with weak governmental control and supervision, which has led to a decline in public order and safety. This research employs a qualitative descriptive method with an analytical approach, using documentation studies, observations, and in-depth interviews with relevant stakeholders. The findings reveal that the implementation of IMB policy has not fully ensured optimal legal protection for the community, particularly regarding public outreach, procedural transparency, and legal certainty over building ownership and usage rights. It was also found that community involvement in the permit process and construction monitoring remains limited. Therefore, legal protection for the public needs to be strengthened through enhanced preventive and repressive government roles, improved regulatory quality, and optimization of the functions of the Investment and One-Stop Integrated Services Office (DPMPTSP). This study recommends regulatory improvements and more extensive public dissemination to realize orderly, safe, and legally compliant development